THE EFFECTS OF HYBRID LEARNING IN ENGLISH READING AT SMA NEGERI 1 BURU - Mukadar, Suraya; AR, Nirwana.; Hajar, Ibnu; Tenriawali, A.Yusdianti (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This study aims to investigate the effect of hybrid learning on the development of students reading comprehension in English Social Studies Class X1C at SMA Negeri 1 Buru Namlea, Buru Island, Maluku Province. This research used a quantitative method by applying an Experimental design, , researchers observed two classes them divided them into the experimental group and the control group class. The findings show that the mean score of the student pre-test in the experimental group was 61.1667, and its standard deviation was 8.47749, while the mean score in the control group was 58.1667, and its standard deviation was 8.65869. The differences mean score between both groups was 3. after treatments were given, the mean score of both groups was significantly different. The mean score of the students post-test in the experimental group was 72.1667, with a standard deviation of 8.57858. On the other side, the mean score of the student post-test in the control group was 63.6667, with a standard deviation 7.30297. The difference in score between both groups was 9, and it means that the mean score of the experimental group is higher than the control group, It also indicates that there is no doubt the use of hybrid learning in reading class is highly effective to achieve learning goals.